2010
DOI: 10.1103/physrevb.82.155141
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Su-Schrieffer-Heeger Hamiltonian for polypyrrole

Abstract: A generic class of Hamiltonians based on the Su-Schrieffer-Heeger ͑SSH͒ model is introduced to address the material-specific properties of conducting polymers beyond polyacetylene. Two physical parameters are incorporated into the original SSH model Hamiltonian, one being the scaling parameter ␥ accounts for the modified electron-phonon coupling strength of aromatic rings and the other parameter representing the attractive cores of heterogeneous atoms, such as NH, S, and O. Their values are uniquely determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 54 publications
0
45
0
4
Order By: Relevance
“…Large variations of the quasiparticle effective mass may simply occur from band structure effects (such as proximity to a van Hove singularity [14,15]), but also from fluctuations which renormalize the band structure. An example is in metals proximate to a density wave instability.…”
Section: Introductionmentioning
confidence: 99%
“…Large variations of the quasiparticle effective mass may simply occur from band structure effects (such as proximity to a van Hove singularity [14,15]), but also from fluctuations which renormalize the band structure. An example is in metals proximate to a density wave instability.…”
Section: Introductionmentioning
confidence: 99%
“…Let H(R) represent the π -electron Hamiltonian describing the PT or PSe systems within the framework of a modified Su-Schrieffer-Heeger (SSH) model [9,10,[19][20][21], where R denotes the geometrical parameters (atom-atom distances) needed for completely defining H(R) in a basis of 2p z orbitals of the carbon atoms and 3p z (4p z ) orbitals of the sulfur (selenium) atoms. The π MOs (φ i ) are formed by linear combination of the carbon 2p z and sulfur 3p z (selenium 4p z ) orbitals:…”
Section: The Methodsmentioning
confidence: 99%
“…It consists of a strong band centered at 260 nm and a weak band around 223 nm. The former originates from the transitions toward the charge transfer state (CTS) corresponding to Eu 3+ -O 2− interactions, the latter may be ascribed to the charge transfer transition from the oxygen ligands to the central metal atoms inside the NbO 4 3− groups [22,26]. Fig.…”
Section: The Luminescent Properties Of Eu 3+ -Doped Y X Gd 1−x Nbo 4 mentioning
confidence: 99%
“…E-mail address: bingyan@tongji.edu.cn (B. Yan). doped with Tb 3+ was synthesized by via the high-temperature solid state method and studied their luminescent spectra [22]; optical properties of YNbO 4 doped with Eu 3+ phosphor was reported that the characteristic emission of rare earth ions Eu 3+ was detected and total or partial quenching of the NbO 4 3− emission occured because of the energy transfer from the matrix to the dopant [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%